(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The rapid digitalization of the economy is fundamentally transforming managerial functions, particularly accounting and business analytics. The widespread adoption of cloud technologies, robotic process automation (RPA), artificial intelligence (AI), blockchain, and big data analytics is redefining the roles of accountants and business analysts, shifting their focus from retrospective data recording to strategic insight generation. The purpose of the article. This article aims to explore the impact of digital transformation on the accounting and analytical functions of enterprises, identify the key technological trends reshaping these professions, and determine the competencies required for professionals to remain relevant and effective in the digital economy. Methods. The research methodology includes a systematic review of recent academic literature and consulting reports (Deloitte, PwC, Gartner, ACCA, Forbes), comparative analysis of traditional versus digital accounting systems, and synthesis of best practices in implementing innovative technologies. Empirical data, expert forecasts, and analytical models were used to assess the potential and challenges of digital integration in financial processes. Results. The study finds that RPA significantly enhances the efficiency and accuracy of routine accounting tasks, enabling professionals to focus on analytical and advisory roles. AI and machine learning support predictive modeling, fraud detection, and scenario planning. Blockchain increases transparency, data immutability, and security in financial transactions, while cloud platforms improve accessibility, scalability, and data integrity. Additionally, modern business analytics evolves into a proactive and prescriptive tool that integrates data from multiple internal and external sources, enabling real-time decision-making and strategic foresight. The roles of accountants and business analysts are converging towards that of data-driven strategic partners, requiring hybrid competencies that merge financial literacy with IT skills, data visualization, and cybersecurity awareness. Conclusions. Digital transformation in accounting and analytics is irreversible and necessitates the rethinking of traditional roles, processes, and education. To remain competitive, enterprises must invest in lifelong learning, IT infrastructure, and corporate cultural adaptation. Professionals must develop hybrid expertise in finance, data science, and business communication. The digital shift is not merely a challenge but a major opportunity for sustainable growth and value creation. Future research should focus on adaptive models of managing accounting systems, integration of diverse data sources, and scenario-based planning supported by predictive analytics tailored to national and international standards.